Patterns of admission in adult medical wards of a district hospital - Mabuza, Patrick Butinyana (My University, 2016)
ABSTRACT BACKGROUND: The study setting was Matikwana Hospital in Mpumalanga Province in South Africa. Matikwana Hospital is a level 1 district hospital situated in Mkhuhlu Township in the Bushbuckridge municipal area at Ehlanzeni District in Mpumalanga. The hospital was facing an unprecedented increase in admissions which in turn was resulting in bed crises in the hospital. This practice led to overcrowding in the wards which, in turn, compromised the quality of healthcare as well as in respect of dignity, privacy and infection control measures. AIM: To describe patterns of admission in the adult medical wards of Matikwana Hospital in Mpumalanga Province for a period of one year from 01 April 201O to 31 March 2011. RESULTS: Records of a total number of 2586 admissions, in the medical wards of Matikwana Hospital during the period from 01 April 2010 until 31 March 2011, were selected for the study through systematic sampling. The gender distribution of participants was not significantly different for both sexes (45.2% for females and 54.8% for males). The mean age of the patients admitted during the study period was 43.2 years. The median was 39 years. The ages of patients ranged from 12 to 100 years. There was a statistically significant difference in patients' age across the gender categories (p-\/alUe 0.0032). A high number of admissions (50.7%) were coming from the Hoxane Traditional Authority which is the area where the hospital is located.. Most patients were admitted with Gastroenteritis (11.4%) followed by Pulmonary Tuberculosis (8.7%) and Lower Respiratory Tract Infection (7.8%) Cases of co-morbidity were also present. Other cases reflected in the top 1O leading causes of admission were Psychosis, Diabetes, Meningitis, Malaria, Anaemia, Tuberculosis and HIV Most patients were admitted and discharged within 4 days (52.6%) whilst 7.3% stayed longer than 14 days (between 14 and 101 days). CONCLUSION: The research identified the catchment areas where most patients are coming from and the type of diseases which are causing the most admissions in the hospital. The other critical issues identified were bed utilisation rate and the average length of stay for patients admitted during the period of study. The findings of this study will assist hospital and district management in planning for resource allocation and for appropriate distribution of healthcare services at community level.
Keywords: Hospitals, District; Nursing Stations